Lessons from a Decade in West Hill: Community Perspective from the Refugee Welcome Center - Tim Doherty; Matthew Klane (Journal of Community Engagement and Scholarship)
This community perspective provides a brief history of the West Hill Refugee Welcome Center (RWC) in Albany, NY, a nonprofit organization that works to (1) assist with long-term refugee resettlement by providing affordable housing and vital services, and (2) address the systemic roots and contemporary repercussions of neighborhood blight. Tim Doherty and the RWC staff detail their various collaborations with local colleges and universities such as SUNY Albany, Russell Sage, and Siena. Faculty from the fields of social work, political science, nutrition, business, education, public health, and more have seen the RWC as a valuable site for student learning and cultural exchange. After highlighting the experiences of specific faculty, students, and refugee neighbors, Doherty and the RWC staff conclude by emphasizing both the inherent value and challenges of this collaborative, interdisciplinary, community-focused, academic work.